The Role of AI in Reducing Healthcare Provider Burnout: A Path to Professional Fulfillment - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Healthcare provider burnout is a global crisis, characterized by emotional exhaustion, depersonalization, and a reduced sense of personal accomplishment 1. W...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Patient Care; Medical Ethics